Design and Construction of a Gold Leaf Electroscope. - Tuyisenge, Julius (Kabale University, 2024)
In developing countries like Uganda, scientific equipment is expensive and generally financially out of reach for most schools, As a result, most schools do not perform well due to a lack of practical skills by learners and improvisational skills by teachers. Electrostatics is one of the most interesting topics to teach and understand if a teacher uses GLE. Conventional GLEs are rare in most rural schools. Improving such an instrument would ease the teaching and learning of Electrostatics. Te study aimed aimed to design and construct a Gold Leaf Electroscope.